The allocation of valenced concepts onto 3D space. Issue 4 (19th May 2018) - Marmolejo-Ramos, Fernando; Tirado, Carlos; Arshamian, Edward; Vélez, Jorge Iván; Arshamian, Artin
ABSTRACT: The valence–space metaphor research area investigates the metaphorical mapping of valenced concepts onto space. Research findings from this area indicate that positive, neutral, and negative concepts are associated with upward, midward, and downward locations, respectively, in the vertical plane. The same research area has also indicated that such concepts seem to have no preferential location on the horizontal plane. The approach–avoidance effect consists in decreasing the distance between positive stimuli and the body (i.e. approach) and increasing the distance between negative stimuli and the body (i.e. avoid). Thus, the valence–space metaphor accounts for the mapping of valenced concepts onto the vertical and horizontal planes, and the approach–avoidance effect accounts for the mapping of valenced concepts onto the "depth" plane. By using a cube conceived for the study of allocation of valenced concepts onto 3D space, we show in three studies that positive concepts are placed in upward locations and near the participants' body, negative concepts are placed in downward locations and far from the participants' body, and neutral concepts are placed in between these concepts in both planes.